Quantification of myocardial blood flow using non–ECG‐triggered MR imaging. Issue 3 (16th September 2014) - Chen, David; Sharif, Behzad; Dharmakumar, Rohan; Thomson, Louise E.J.; Bairey Merz, C. Noel; Berman, Daniel S.; Li, Debiao
<x xml:space="preserve">Abstract</x> Purpose MR myocardial perfusion imaging is dependent on reliable electrocardiogram (ECG) triggering for accurate measurement of myocardial blood flow (MBF). A non–ECG‐triggered method for quantitative first‐pass imaging may improve clinical feasibility in patients with poor ECG signal. The purpose of this study is to evaluate the feasibility of a non–ECG‐triggered method for myocardial perfusion imaging in a single slice. Methods The proposed non–ECG‐triggered technique uses a saturation‐recovery magnetization preparation and golden‐angle radial acquisition for integrated arterial input function (AIF) measurement. Image based self‐gating with a temporal resolution of 42.6 ms is used to generate a first‐pass image series with consistent cardiac phase. The AIF is measured using beat‐by‐beat T1 estimation of the ventricular blood pool. The proposed technique was performed on 14 healthy volunteers and compared against a conventional ECG‐triggered dual‐bolus acquisition. Results The proposed method produced MBF with no significant difference compared with ECG‐triggered technique (mean of 0.63 ± 0.22 mL/min/g to 0.73 ± 0.21 mL/min/g). Conclusion We have developed a non–ECG‐triggered perfusion imaging method with T1 based measurement of the AIF in a single slice. In this preliminary study, our results demonstrate that MBF measured using the proposed method is comparable to the conventional ECG‐triggered method. Magn Reson Med 74:765–771, 2015. © 2014 Wiley Periodicals, Inc.